Psychological profile of university students - Elias, Habibah; Noordin, Nooreen; Mahyuddin, Rahil (Universiti Putra Malaysia Press, 2011)
Psychosocial Profile of University Students is a valuable professional reference for educators and students. The purpose of this book is to present the findings of a research done on first and second year university students in two public universities and two private universities situated in the Klang Valley. This book helps educators and university administrators to understand Malaysian university students’ behavior profile based on psychosocial variables such as academic adjustment, selfefficacy, achievement motivation, self-esteem, emotional intelligence and academic achievement. This book consists of eight chapters with each chapter focusing on a different aspect of the research. The findings reported in this book are useful for university staff and students to understand the type of problems faced by students especially in the initial years in university and the type of assistance that should be given in order for them to be better adjusted and perform well in their studies. With knowledge on the psychosocial profile of university students, it is hoped that educators and university authorities will take appropriate actions in guiding students to realize their potentials and contribute to the national development.